Family demography in Asia a comparative analysis of fertility preferences - Gietel-Basten, Stuart; Casterline, John B.; Minja, Kim Choe 1941- (Cheltenham, UK Edward Elgar Publishing, 2018)
The demographic future of Asia is a global issue. As the biggest driver of population growth, an understanding of patterns and trends in fertility throughout Asia is critical to understand our shared demographic future.
Keywords: Family demography -- Asia; Fertility, Human -- Social aspects -- Asia